2022
DOI: 10.1186/s40878-022-00288-y
|View full text |Cite
|
Sign up to set email alerts
|

Extending mixed embeddedness to a multi-dimensional concept of transnational entrepreneurship

Abstract: Migrant entrepreneurship in times of transnational migration go beyond locally serving markets and increasingly operate transnationally. The mixed embeddedness by Kloosterman and Rath has become the main concept to analyze such migrants’ entrepreneurship as it accounts for the multiple embeddedness of entrepreneurs in the variety of social and institutional contexts at multiple levels. This concept, however, does not yet accommodate the transnational dimensions of migrant entrepreneurship, which is still rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
1
17
0
5
Order By: Relevance
“…This study refers that macroeconomic regulation can drive people's enthusiasm for starting a business, and people will provide certain conditions for starting a business with the growth of macroeconomics and their own actual conditions. And, with the support of this entrepreneurial condition, a series of entrepreneurial behaviors are formed (Yamamura and Lassalle, 2022). In addition, previous studies have also shown that economic recession can have a significant impact on entrepreneurial intentions and behavior, and it also affects entrepreneurial psychology (Yang et al, 2021).…”
Section: Macroeconomics and Farmers' Entrepreneurial Behaviormentioning
confidence: 92%
“…This study refers that macroeconomic regulation can drive people's enthusiasm for starting a business, and people will provide certain conditions for starting a business with the growth of macroeconomics and their own actual conditions. And, with the support of this entrepreneurial condition, a series of entrepreneurial behaviors are formed (Yamamura and Lassalle, 2022). In addition, previous studies have also shown that economic recession can have a significant impact on entrepreneurial intentions and behavior, and it also affects entrepreneurial psychology (Yang et al, 2021).…”
Section: Macroeconomics and Farmers' Entrepreneurial Behaviormentioning
confidence: 92%
“…Indeed, many sociological theories tend to be vernacularly used in entrepreneurship, cherry-picking concepts as buzz words is a common phenomenon, if not symptomatic of social theories in entrepreneurship. Examples of such superficial engagement with social theories in entrepreneurship are reflected: in the singular usage of social capital and claiming it to be Bourdieusian (whereas Bourdieu's theory is unique and pivotal as it embeds different types of capital into their specific field, see Yamamura and Lassalle (2022); Bourdieu 1976, 1979; Robinson et al, 2021), the mere counting of ethnicities of entrepreneurs and claiming it to be superdiversity (whereas Vertovec's concept precisely criticises this groupist view and extends the diversity dimensions beyond ethnicity, see Yamamura and Lassalle (2020a); Vertovec, 2007) and in the limited adaptation of Crenshaw’s (1991) intersectionality theory into entrepreneurship (often ignoring the important discourses on power issues and simultaneous multiple discrimination in social sciences) when a real engagement with intersectionality theory is needed (Essers et al, 2020; Lassalle and Shaw, 2021b; Yamamura and Lassalle, 2021).…”
Section: Against Methodological Individualism …For Sociological Appro...mentioning
confidence: 99%
“…We approach our study by deploying a concept-centric systematic literature review as recommended by some scholars (Levy and Ellis, 2006; Webster and Watson, 2002; Rowe, 2014; Paré et al , 2017; Okoli, 2015; Schryen, 2013). A systematic literature review provides detailed steps, identifying, analysing, evaluating and interpreting prior relevant studies in a given area of interest (Castro and Zermeño, 2020; Chan and Mustafa, 2020; Ahmad and Bajwa, 2021; Aldairany et al , 2018; Aljuwaiber, 2020; Hänle et al , 2021; Khan et al , 2022; Sharma, 2018; Santisteban and Mauricio, 2017; Claire et al , 2019; Yamamura and Lassalle, 2022; Bansal et al , 2020). Consequently, it provides a rigorous process, free of biases and the credible outcome needed by researchers as a foundation for advancing knowledge (Webster and Watson, 2002; Okoli, 2015; Mahdavi, 2011).…”
Section: Systematic Literature Review Methodologymentioning
confidence: 99%